2008
DOI: 10.1001/jama.299.8.925
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Blood-Derived and Marrow-Derived Stem Cells for Nonmalignant Diseases

Abstract: TEM CELLS ARE UNDIFFERENTIated cells that through replication have the capability of both self-renewal and differentiation into mature specialized cells. In broad terms, there are 2 types of stem cells, embryonic stem cells and adult stem cells. Human embryonic stem cells are isolated from a 50-to 150-cell, 4-to 5-dayold postfertilization blastocyst. Embryonic stem cells generate every specialized cell in the human body and, while capable of indefinite ex vivo proliferation, exist only transiently in vivo (dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
214
0
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(226 citation statements)
references
References 110 publications
1
214
0
11
Order By: Relevance
“…The rationale of these therapeutic approaches is to eradicate pathogenic cells responsible for the disease development while sparing the pluripotent blood stem cells from any ill effect and immune reset, that is, to generate new selftolerant lymphocytes after chemotherapy elimination of self or auto-reactive lymphocytes. 11,30 Despite the previous knowledge concerning the effects of chemotherapy and HSCT, the role of BM-derived cells in the intestine after transplantation is presently unclear. Both in animal models as well as in patients, it seems that BMCs are involved in the healing process after intestinal injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale of these therapeutic approaches is to eradicate pathogenic cells responsible for the disease development while sparing the pluripotent blood stem cells from any ill effect and immune reset, that is, to generate new selftolerant lymphocytes after chemotherapy elimination of self or auto-reactive lymphocytes. 11,30 Despite the previous knowledge concerning the effects of chemotherapy and HSCT, the role of BM-derived cells in the intestine after transplantation is presently unclear. Both in animal models as well as in patients, it seems that BMCs are involved in the healing process after intestinal injury.…”
Section: Discussionmentioning
confidence: 99%
“…11,30 Therefore, these evidences suggest that SCT could be justified in some patients with IBD, which have already begun to be transplanted in some current trials, 42,43 thus raising the question of whether the cell transplantation or the intense immunosuppression was the critical event for patient recovery. In our study, both therapeutic approaches induced remission of the disease and, although we did not elucidate the exact mechanisms of action of the graft in the treatment of the IBD, we showed that in this model, the infusion of the graft was extremely important to reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical setting, cell therapies have been previously used in patients with ischemic heart disease, both in the acute and chronic stages. In most trials, the mononuclear fraction of bone marrow has been used, but a variety of cell types from bone marrow and skeletal myoblasts have also been delivered to patients (10)(11)(12)(13)(14)(15)(16)(17). Results have demonstrated excellent safety with encouraging signs of clinical improvement (10)(11)(12)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Autologous hematopoietic stem cell (HSC) transplantation is an established treatment for hematological malignancies, and recently has been employed to treat severe chronic autoimmune diseases (CAID), 1 including newly diagnosed type 1 diabetes mellitus (T1DM). 2 The objective of this modality of treatment in autoimmune diseases is the elimination of autoreactive clones of T cells to allow the regeneration of a 'new' immune system from the HSC infused.…”
mentioning
confidence: 99%